MULTIFUNCTION TOOLS OF PHYSICAL EDUCATION, SPORTS AND HEALTH AT ELEMENTARYSCHOOL (The Journal of Educational Development, 2014)
This research is aimed at developing and resulting a multifunction tool and an example of effective learning which is acceptable for Physical Education, Sports and Health learning for Elementary students. This research is model development of the learning tool for elementary students.Â  This research is conducted in several stages: 1) designing draft of initial product, 2) expert validation, 3) small scale trial, 4) First stage revision, 5) Large scale trial, and 6) Second Stage revision (Final revision). The results of the research are: 1)development of multifunction tools. 2) the result of product effectiveness test at SD Negeri 2 Trimodadi, SD Negeri 2 RatuAbungdan SD Negeri 1 RatuAbung is obtained at the average of pulse increase about 62,81%. 3) The test result of product acceptability on internal and external aspect is at the average of 94,58%.